Tujuan Pendidikan Islam dan Tujuan Hidup Manusia - Radjaming, Nawir (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2024)
In human life, education is a fundamental thing and needs attention, because education is a serious effort to preserve certain life values both in the personal, family and community environment. The aim of writing this paper is to provide an explanation of the aims of Islamic education and the aims of human life created by Allah SWT. As for the usefulness of this paper, we can study more deeply the essence of Islamic education in relation to the purpose of human creation so that the education carried out can achieve effective and efficient results in accordance with our shared hopes, guided by the Koran and the hadith of the Prophet SAW. A goal is something that will be achieved with an effort. Education in a broad sense is the process of changing and separating cultural values for each individual in a society. This human task is also the goal of life that must be carried out in order to achieve happiness in this world and the afterlife. Based on this description, a conclusion can be drawn as the core of the discussion of this article, namely as follows: Education is all activities carried out deliberately and programmed to achieve a goal, Islamic education is an ideal education, education that harmonizes physical and mental growth, physical and spiritual, individual and community development as well as happiness in the world and the hereafter, Islamic education aims to realize happiness as well as the purpose of human life created by Allah on this earth, besides worshiping Him.